2022
DOI: 10.1002/anie.202201093
|View full text |Cite
|
Sign up to set email alerts
|

N‐Heterocyclic Carbene Based Nanolayer for Copper Film Oxidation Mitigation

Abstract: The wide use of copper is limited by its rapid oxidation. Main oxidation mitigation approaches involve alloying or surface passivation technologies. However, surface alloying often modifies the physical properties of copper, while surface passivation is characterized by limited thermal and chemical stability. Herein, we demonstrate an electrochemical approach for surfaceanchoring of an N-heterocyclic carbene (NHC) nanolayer on a copper electrode by electro-deposition of alkyne-functionalized imidazolium cation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 62 publications
0
19
0
Order By: Relevance
“…Thus, the newly developed radical initiator NHC15AZO SAMs with hairpin conformations on the surface of gold provide convenient platforms for growing surface-initiated polymers in which the film thickness can be tuned simply by adjusting the reaction time. Importantly, the growth of these films can be tuned to give markedly greater polymer thicknesses than those generated using other NHC-based adsorbates (e.g., 250 nm vs 2 nm). , …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, the newly developed radical initiator NHC15AZO SAMs with hairpin conformations on the surface of gold provide convenient platforms for growing surface-initiated polymers in which the film thickness can be tuned simply by adjusting the reaction time. Importantly, the growth of these films can be tuned to give markedly greater polymer thicknesses than those generated using other NHC-based adsorbates (e.g., 250 nm vs 2 nm). , …”
Section: Resultsmentioning
confidence: 99%
“…In fact, the Crudden group found that SAMs generated from NHCs are more chemically, thermally, and electrochemically stable than thiol-derived SAMs on gold . Despite these attractive features, the major drawback to forming SAMs on gold via carbene adsorption is the contamination of residual amines from the strong bases (e.g., KHMDS) used to produce free carbenes; such residues limit the formation of well-ordered SAMs because these residual amines can bind strongly to the metal surface. , The most successful efforts to overcome this disadvantage have been concentrated on using “masked NHCs”, which can generate free carbenes without the use of strong bases . Specifically, the Crudden group reported the preparation and deposition of benzimidazolium hydrogen carbonate salts, which are “masked NHCs”, on gold surfaces. ,, In these studies, bench-stable NHC bicarbonate-based adsorbates were prepared via ion-exchange.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among these metals, copper, an abundant and inexpensive first-row transition metal, is historically one of the most commonly employed in the development of technological applications. The functionalization of oxidized copper surfaces is challenging because the attachment of organic molecules leads to reduction. At the same time, many efforts have been made to avoid further oxidation of copper using thiols or, recently, NHC ligands. In photocatalysis, copper oxide is a widely used material and the attachment of organic molecules can be very beneficial …”
mentioning
confidence: 99%